THE INFLUENCE OF GREEDY, OPPORTUNITY, NEED AND EXPOSURE ON STUDENTS' ACADEMIC CHEATING PERFORMANCE: (Survey on Students of the Faculty of Teacher Training and Education Class of 2020, Universitas Siliwangi) - Rosma, Ayu; Solihat, Ai Nur; Gumilar, Gugum (Transpublika Publisher, 2023)
This study seeks to examine how students' academic cheating behavior is influenced by factors such as greed, opportunity, need, and exposure. The research employs a quantitative survey approach with an explanatory research design. The study population comprises 1,289 active students from the Faculty of Teacher Training and Education at Siliwangi University, who are members of the class of 2020. A Proportional Random Sampling technique was used, resulting in a sample size of 305 respondents. Data was collected through questionnaires, and data analysis included multiple linear regression analysis, as well as partial and simultaneous hypothesis testing. The findings indicate that while greed does not significantly impact students' academic cheating behavior (p = 0.105), opportunity has a significant effect (p = 0.000), need also plays a significant role (p = 0.031), and exposure does not have a significant influence (p = 0.252). Additionally, when considering all these factors together, greed, opportunity, need, and exposure collectively have a significant impact on students' academic cheating behavior (p = 0.000).